Experimental study on emodin regulating the proliferation of oral squamous cell carcinoma cells through autophagy - XIONG Ke, ZHANG Hao, HU Tuqiang (Kouqiang yixue, 2024)
Objective To investigate the effect and mechanism of emodin on cell proliferation in OSCC. Methods CAL-27 cells and SCC-15 cells were intervened with different concentrations of emodin, and the proliferative activity of the cells was detected by CCK-8 method, and the appropriate concentration was screened for follow-up experiments. The colony formation experiment helped detect the colony formation ability. The expressions of PCNA, Beclin1 and LC3 were detected using Western blot. After treating the cells with rapamycin and emodin, the cell proliferation activity and the colony formation ability were examined. PCNA, Beclin1 and LC3 expressions were detected. The tumor formation experiment helped detect the effect of emodin on tumor weight and volume in nude mice. The liver and kidney structure in nude mice was observed using HE staining. Moreover, the PCNA and Beclin1 protein expression was detected by IHC. Results Emodin could significantly decrease the proliferative activity and aggregation ability of CAL-27 cells in a concentration-dependent manner. Emodin could down-regulate the PCNA, Beclin1, and LC3Ⅱ/LC3Ⅰ expression levels. RAPA could reverse the inhibitory effect of emodin on cell proliferation. Emodin had no significant hepatorenal toxicity and could reduce the volume and mass of the tumor and down-regulate the expression of PCNA and Beclin1 protein inside the tumor. Moreover, the expression of PCNA and Beclin1 in tumor showed a certain positive correlation. Conclusion Emodin can inhibit oral squamous cell proliferation, and its effect may be associated with autophagy inhibition.